Enhancing Food Security In West Java In The Context of Achieving Sustainable Development Goals - Lesmana, Vanny Fraditha; Hanifah, Anggi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Food security in West Java is an important issue that is often overlooked. However, there are still many inhibiting factors affecting the development of food security in the region. This study employs a quantitative method using a questionnaire as an instrument to collect data. Out of 127 respondents, the majority identified economic and political stability as the main factors hindering the development of food security, followed by poverty rates and infrastructural limitations. Other factors such as climate change and land degradation were also mentioned as significant hindrances. In this context, understanding these inhibiting factors is crucial in designing comprehensive strategies to enhance food security in West Java, thus contributing to the realization of the Sustainable Development Goals (SDGs), particularly SDG 2, Zero Hunger.